Pneumocystis jirovecii pneumonia in solid organ transplant recipients: a descriptive analysis for the Swiss Transplant Cohort. Issue 6 (19th September 2018) - Neofytos, Dionysios; Hirzel, Cedric; Boely, Elsa; Lecompte, Thanh; Khanna, Nina; Mueller, Nicolas J.; Boggian, Katia; Cusini, Alexia; Manuel, Oriol; van Delden, Christian
Abstract: Background: Descriptive data on Pneumocystis jirovecii pneumonia (PJP) in solid organ transplant recipients (SOTr) in the era of routine Pneumocystis ‐prophylaxis are lacking. Methods: All adult SOTr between 2008 and 2016 were included. PJP was diagnosed based on consensus guidelines. Early‐onset PJP was defined as PJP within the first‐year‐post‐transplant. Results: 41/2842 SOTr (1.4%) developed PJP (incidence rate: 0.01/1000 person‐days) at a mean of 493‐days post‐transplant: 21 (51.2%) early vs 20 (48.8%) late‐onset PJP. 2465 (86.7%) SOTr received Pneumocystis ‐prophylaxis for a mean 316 days. PJP incidence was 0.001% and 0.003% (log‐rank < 0.001) in SOTr with and without Pneumocystis ‐prophylaxis, respectively. PJP was an early event in 10/12 (83.3%) SOTr who did not receive Pneumocystis ‐prophylaxis and developed PJP, compared to those patients who received prophylaxis (11/29, 37.9%; P ‐value: 0.008). Among late‐onset PJP patients, most cases (13/20, 65%) were observed during the 2nd year post‐transplant. Age ≥65 years (OR: 2.4, P ‐value: 0.03) and CMV infection during the first 6 months post‐SOT (OR: 2.5, P ‐value: 0.006) were significant PJP predictors, while Pneumocystis ‐prophylaxis was protective for PJP (OR: 0.3, P ‐value: 0.006) in the overall population. Most patients (35, 85.4%) were treated with trimethoprim‐sulfamethoxazole for a mean 20.6 days. 1‐year mortality was 14.6%. Conclusions: In the Pneumocystis ‐prophylaxis‐era, PJP remains a rare post‐transplant complication. Most cases occurred post‐PJP‐prophylaxis‐discontinuation, particularly during the second‐year‐post‐transplant. Additional research may help identify indications for Pneumocystis ‐prophylaxis prolongation.